Strategi Implementasi Peningkatan Mutu Lembaga Pendidikan Berdasarkan Konsep Edward Deming - Siti Lutfiachi Zar’an (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Improving the quality of educational institusions is an important priority in facing the challenges of globalization and technological developments. This article examines implementation strategies for improving the quality of educational institutions using Edward Deming’s quality concept, which focuses on a systematic and sustainable approach. This concept emphasizes the importance of leadership, involvement of all parties, and the use of data for fact-based decision making. Deming’s approach, which consists of 14 principles, such as continuous improvement, effective training, and eliminating barriers between departments, provides practical guidance for administrators of educational institutions to improve the quality of service. This article also discusses the obstacles that may be faced in implementing this concept and solutions to overcome them. By adopting Deming’s concept, educational institutions are expected to be able to create a quality culture that is consistent and relevant to society’s needs.